Hubungan Korelasi di antara Potensi C Biomassa dengan Indeks Kualitas Tanah Pada Berbagai Tipe Penggunaan Lahan Kering di Kabupaten Aceh Besar: Hubungan Korelasi di antara Potensi C Biomassa dengan Indeks Kualitas Tanah Pada Berbagai Tipe Penggunaan Lahan Kering di Kabupaten Aceh Besar - Rachmat Hidayat; Umar Husein Abdullah; Ruhalena Wilis; Nurlia Farida (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Various characteristics of land use and plant canopy density will result in different soil physical qualities and groundwater transfer capacities, affecting groundwater reserves, drainage, runoff, and erosion, as well as agricultural output. Naharuddin, 2018; Risamasu and Marlissa, 2020; Naharuddin et al., 2020). This study aims to determine the correlation between the C potential of biomass and the soil quality index (IKT) on various types of dry land use in Aceh Besar district. This research was carried out on a unit of land in a dry area in Aceh Besar district with a study area of 239,439.63 ha. Analysis of biomass samples and soil samples was carried out at the Laboratory of Soil and Plant Sciences and Soil Physics Laboratory, Faculty of Agriculture, University of Syiah Kuala. The partners of this community service activity are students of the Indonesian Polytechnic and students of the Agrotechnology study program at Iskandar Muda University. The relationship between potential C Biomass and soil quality index is in a strong correlation. It is hoped that all students of the Venezuelan Indonesian Polytechnic and students of Agrotechnology at Iskandar Muda University. be able to understand how to take samples of biomass and soil and be able to use the SPSS 24 program or Microsoft Excel to process the results of the correlation test. For further community service, other soil fertility parameters are also calculated which are related to the soil quality index for different regions.